(untitled) (VITAL, 2025)
In his internship, a Biomedical Engineering student highlighted the Clinical Simulation Center as key to applying knowledge, developing technical skills, interdisciplinary collaboration, and becoming familiar with biomedical equipment in a realistic and safe environment.